Frida Kahlo - Venezia, Mike. (New York : Children's Press, 1999)
Discusses the life of Mexican painter Frida Kahlo, including her childhood, her art, and her marriage to Diego Rivera.
G6
Keywords: Kahlo, Frida -- Juvenile literature; Kahlo, Frida; Painters -- Mexico -- Biography -- Juvenile literature; Artists; Women -- Biography